Menelaah Antroposentris Dalam Menyikapi Krisis Lingkungan Dari Perspektif Teologi Penciptaan - Lolangion, Feldy; Runturambi, Marselino Cristian; Kawuwung, Jefry (Institut Agama Kristen Negeri Manado, 2021)
This article was written with the aim of understanding the environmental crisis from the perspective of creation theology, particularly with regard to the anthropocentric understanding of society when looking at nature. In this article, researchers examine human perspectives on nature, then proceed to things that affect people's state of mind by harnessing nature, and end with an ecological study of the theology of creation. The method used is qualitative research with a descriptive approach. Research sources use literature survey techniques and narrative criticism to explore concepts of creation theology by examining anthropocentric understanding for dealing with environmental crises. So that we can describe that the reinterpretation of the theology of creation is a way of dealing with anthropocentric concepts.